Effect of autoclave devitalization on autograft incorporation and bone morphogenetic protein of tibia in Sprague-Dawley rats (Medical Journal of Indonesia, 2014)
Background: Heating process with autoclave is one of limb salvage modalities that are widely used. but the results are not satisfying, due to mechanical bone fragility. However, considering this treatment modality is widely accepted in terms of financial, religion and sociocultural aspects, we conducted a on study rats treated with resection and reconstruction with autoclave heating method to assess bone healing by sequential radiology, histopathologic osteoblasts count, and bone morphogenetic protein (BMP). Methods: Thirty six Sprague-Dawley rats were divided into two groups with one group being the autoclave group and others served as control group. In both groups, the tibial diaphysis was extracted en bloc for 7 mm. All groups were kept for 8 weeks and treated under the same condition except the autoclave group, where the extracted bones were put into autoclave at 134°C for 15 minutes and refixed again with k-wire. We performed radiological examination at 5th and 8th week using Lane and Sandhu radiological score. After extraction, the tibial bones were inspected for histological pattern using Salked modified score, osteoblast quantity counting and BMP-2 values. Results: There were statistically significant diffences between control and autoclave group on radiological score at 5 th (5.12 ± 1.6 g vs 3.21 ± 2.42, p = 0.023) and 8 th week (6.06 ± 1.71 vs 4.29 ± 2.53, p = 0.040), histological score between groups (6.06 ± 1.14 vs 4.14 ± 1.99, p = 0.005), osteoblast count (p < 0.001), and BMP-2 expression, respectively. Conclusion: Autoclave recycling autograft lowered the speed of graft incorporation and BMP-2 expression. Therefore, autoclave recycling autograft as a method of limb salvage surgery must be reevaluated and not considered to be applied for treatment in bone malignancy.